2011
DOI: 10.1037/a0024941
|View full text |Cite
|
Sign up to set email alerts
|

Marriage as a risk factor for internalizing disorders: Clarifying scope and specificity.

Abstract: Objective Marital discord has been linked to both depression and anxiety; however, our understanding of how marriage contributes to the development of internalizing symptoms is limited in scope and lacking specificity. First, it is unclear whether the marital relationship contributes to the broad dimension of internalizing symptoms as opposed to specific diagnoses. Second, it is unclear how the marital relationship contributes to internalizing symptoms: through global marital dissatisfaction or through specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 81 publications
2
30
2
1
Order By: Relevance
“…Perhaps other aspects of intimate relationships represent key protective factors to be examined. For example, recent research has demonstrated the relative importance of having a strong emotional bond with one’s partner during the transition into marriage for the mental health of women (Brock & Lawrence, 2011; Brock & Lawrence, 2014a). Indeed, emotional intimacy—closely related to support but also a distinct construct—predicts depressive and anxiety symptoms during the first seven years of marriage, beyond the effects of enduring vulnerabilities (i.e., neuroticism) and stress external to the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps other aspects of intimate relationships represent key protective factors to be examined. For example, recent research has demonstrated the relative importance of having a strong emotional bond with one’s partner during the transition into marriage for the mental health of women (Brock & Lawrence, 2011; Brock & Lawrence, 2014a). Indeed, emotional intimacy—closely related to support but also a distinct construct—predicts depressive and anxiety symptoms during the first seven years of marriage, beyond the effects of enduring vulnerabilities (i.e., neuroticism) and stress external to the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Most people experience conflicts in their communications as infinitely intensive (Halford, 2001;HoltLunstad, & Birmingham, 2008). Conflicts are also positively correlated with inappropriate psychological well-being conditions (Galinsky and Waite, 2014;Hawkins, & Booth, 2005), insecure attachment style (Gouin, 2009), several psychiatric disorders such as internalizing disorders (Brock, & Lawrence, 2011), depression (Wang , Wang , & Miller 2014), anxiety disorders (Doss, Simpson, & Christensen, 2004), sexual dysfunction disorders (Metz, & Epstein, 2002), and physical health problems (Galinsky and Waite, 2014) such as hypertension (Holt-Lunstad, & Birmingham, 2008), chronic pain (Cano et al, 2004) and ischemic heart diseases (Galinsky and Waite, 2014). The more unsatisfied the spouses are with their marital status, the higher is the probability of divorce (Gottman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Brock & Lawrence (2011) demonstrated univariate associations among four relationship processes (conflict, support, emotional intimacy, power/control) and internalizing symptoms; however, when examining the simultaneous effects of these variables on symptoms, control was associated with husbands’ symptoms whereas (low) emotional intimacy was associated with wives’ symptoms. This study represents an important step in identifying the aspects of the marital relationship contributing to individual psychopathology; however, it is unclear whether these relationship processes represent predictors of symptoms when considered in the context of their complex relations with key diatheses and stressors (neuroticism and chronic stress).…”
Section: The Present Studymentioning
confidence: 84%